An Integrated Supply Chain Model for Educational Management for Higher Education Institutions in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim is develop and to evaluate of an integrated supply chain model for educational management for higher education institutionsin Thailand.The sample group of 10 expert consisted of three experts on supply chain , two expert on curriculum, three expert on Educational Research and Evaluation and two expert on management,The expert selected by purposive sampling. All experts must have educational qualification at the doctoral degree level, and must have more than two years of work experience The statistical methods used in the research are arithmetic mean and standard deviation. The research findings show thatintegrated supply chain model for educational management for higher education Institutionsin Thailandcomprises six principal, namely, main components Suppliers, service provider,customer, finished product and consumer.The overall evaluation result an integrated supply chain model for educational management for higher education institute in Thailandshows the overall arithmetic mean of 3.60 andstandard deviation of 0.64.Suggesting thatan integrated supply chain model for educational management for higher education Institutions in Thailandto be appropriately applied in actual work settings.